Where Are the Risks? An Assessment of Recent Developments in Mediation Confidentiality. Issue 11 (December 2016) - Ziegler, Richard F.
Abstract : Confidentiality is a key ingredient in a successful mediation. Not surprisingly, mediation agreements typically provide for stringent confidentiality protection, prohibiting the participants from any subsequent disclosures of information shared in the course of the mediation process.